Chemistry Textbook Analysis Based on Science Literacy - Yuli Iswanti; Maria Ulfa; Sulistyo Saputro; Sri Yamtinah; Mohammad Masykuri; Bakti Mulyani; Ari Syahidul Shidiq; Agung Nugroho Catur Saputro (Postgraduate, University of Mataram, 2024)
This research is included in the type of qualitative descriptive research that is used to analyzing the content of science literacy in chemistry textbooks for class XI SMA Negeri in Surakarta. The book that was selected using the purposive sampling technique is textbook chemistry used by public high schools in Surakarta. The science literacy category consists of four categories, which is science as a body of knowledge, science as a way of investigation, science as a way of thinking, and the interaction of science, technology, and society. Category fulfillment results in science literacy in book A has a ratio of the first category: second category: third category: the fourth category is 5:2:3:0. The ratio in book B is 6:2:2:0, the ratio in books C and D are 7:1:1:0, and the ratio in book E is 7:0:2:0. From the results of the study, it can be concluded that book A is closest to the ideal standard of the ratio of science literacy categories according to Wilkinson (1999) which is 4:2:2:2.